2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5160686
|View full text |Cite
|
Sign up to set email alerts
|

Control of many robots moving in the same direction with different speeds: A decoupling approach

Abstract: This paper considers the problem of controlling a group of microrobots that can move at different speeds but that must all move in the same direction. To simplify this problem, the movement direction is made a periodic function of time. Although the resulting control policy is suboptimal for an infinite-horizon quadratic cost, a bound is provided on how suboptimal it is. This bound is extended to show that, in theory, the design compromise making all robots move in the same direction only increases the expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The authors have demonstrated limited independent control of two microrobots with a single global input. DeVon and Bretl [51] have developed a controller that is capable of moving multiple heterogenous Magmites towards a specific direction with different speeds.…”
Section: Multi-microrobot Control Using Magnetic Fieldsmentioning
confidence: 99%
“…The authors have demonstrated limited independent control of two microrobots with a single global input. DeVon and Bretl [51] have developed a controller that is capable of moving multiple heterogenous Magmites towards a specific direction with different speeds.…”
Section: Multi-microrobot Control Using Magnetic Fieldsmentioning
confidence: 99%
“…By introducing non-uniformity in the robots, the authors managed to obtain the control of two different robots. DeVon and Bretl [63] have developed a controller for these microbots with carefully introduced heterogeneity that is able to move the robots in different speeds to the desired directions with same global input. However, an inherit coupling of the robot behavior still exists when exploiting homogeneity.…”
Section: Independently Controllable Microswarmsmentioning
confidence: 99%
“…To obtain independent control, there have been various approaches that introduce heterogeneity into the robots so that they can be affected by the same field in a significantly different fashion [37]- [39]. In this way, controllers can be developed that can control multiple robots somewhat independently of each other with the same global input [40]. Another approach is to utilize the influence zone of a particular magnetic coil and partition the workspace accordingly so that identical robots can be controlled by dedicated coils without affecting the others [41].…”
Section: A Related Workmentioning
confidence: 99%